PENERAPAN MODEL PEMBELAJARAN PICTURE AND PICTURE MELALUI MEDIA GAMBAR PADA SUBTEMA KESIAPSIAGAAN GEMPA BUMI UNTUK KETUNTASAN HASIL PEMBELAJARAN ANAK TK NURUL IMAN LHOKSEUMAWE - Erlinawati .; Khairuddin .; Nyak Amir (Jurnal Ilmu Kebencanaan : Program Pascasarjana Unsyiah, 2016)
Children learning outcomes with the theme Sub theme of earthquake relief group B TK Nurul Iman Lhokseumawe has not reached the Minimum Exhaustiveness Criteria set. This is because the child is not interested in the material presented by the teacher because they do not use the appropriate model and media in the Teaching and Learning Process. This study aims to improve learning outcomes Earthquake Preparedness in children group B TK Nurul Iman Lhokseumawe through the application of the model of learning picture and picture by using the image media. The hypothesis of action with the application of the model of learning picture and picture through the media images can provide a complete learning outcomes of children's group B TK Nurul Iman Lhokseumawe. This type of research is a classroom action research (PTK) conducted in two cycles. Research subjects are all students of B grade TK Nurul Iman Lhokseumawe academic year 2015/2016 as many as 26 children. The design of the research by preparing a research report, providing the image media and preparing a research report plan. Technique of collecting data using observation sheet. Data analysis techniques using qualitative descriptive with complete and incomplete criteria. The conclusion is based on the results of the research is the hypothesis of action in this research accepted the truth that is with the application of learning models Picture and Picture by using the media images in the sub theme of earthquake preparedness can reach the criteria of completeness at least 76 in children group B TK Nurul Iman Lhokseumawe